Small Glass Bottles in the Shape of Date Fruit from the Zadar Area (Archaeologia Adriatica, 2017)
The paper studies six small relief glass bottles in the shape of date fruit, unearthed in grave contexts in the broader Zadar area. They are part of a larger group of anthropomorphic, zoomorphic and phytomorphic glass artefacts produced in the course of the 1st and 2nd centuries. These are artefacts blown in two-part moulds with a subsequently worked neck and rim, and a body covered with wavy folds imitating the skin of ripe dates. Depending on whether the ribbing was more stylised or more realistic, such artefacts are classified into two variants: hyperrealistic and stylised specimens. The realistic appearance of many small bottles in the shape of date fruit, which is partly due to their ornamental relief style, and also partly their colour, which is mostly yellowish, brown, brown-red or amber, has led certain authors to the conclusion that real fruit was used for the production of the moulds. Their popularity, or rather the popularity of their content, is confirmed by their wide distribution across the area of the Empire, including the Zadar region. Given that the majority of specimens have been found in the Eastern Mediterranean, this area has been determined as the site of their production. Although statistics can be a misleading criterion for determining the location of workshops, in this instance it is confirmed not only by the widespread production of glass artefacts by means of mould-blowing in the Eastern Mediterranean area, but also by the popularity of dates in this region, as confirmed by numerous antique sources.
Keywords: Zadar area; Roman glass; small date-shaped bottles